Creativity and mystical experiences among artistically gifted young people - Radoń, Stanisław (Studia Psychologica: Theoria et praxis, 2010)
This article examines the role of creativity on mystical experiences among artistically gifted young people. Ss (N=150 aged 15-20 yrs) were administered ąuestionnaire measures four aspects of creativity (Popeks CreativeBehaviour Questionnaire KANH-I) and eight of religious experience {Hood ’s Mysticism Scalę). K-Means Cluster analysis and multiple regression were used (SPSS). The effects of psychological analysis suggests that creativity is important factor on mystical experience especially on creative persons (higher intensification of creativity increase mystical experiences on tree aspects ofmysticism: timelessness p=0,001, inner subjectivity p=0,015, ineffability p=0,0 43) and on women (four aspects of mysticism: timelessness p=0,001, inner subjectivity p=0,017, ineffability p=0,036, positive affect p=0,049). On men is limited to one aspect of mysticism (the feeling of holy p=0,001). The results suggest that creativity may be important variable to consider within the theory of religious experience.